Preliminary Phytochemical Screening, Identification of Some Bioactive Constituent and Isolation of Unknown Compound from Murraya paniculata Cultivated in Iraq - Zainab Ali Qasim; Amjed Haseeb Khamees (Iraqi Journal of Pharmaceutical Sciences)
Murraya paniculata, sometimes known as orange Jessamine, is a significant decorative plant found in tropical and subtropical regions. It belongs to the Rutaceae family. The distribution of this species extends from South Asia to Australia. This plant possesses a multitude of applications in traditional medicine for the treatment of several ailments. The plant demonstrates an extensive array of pharmacological actions, involving antinociceptive, antioxidant, anti-diabetic, antibacterial, and analgesic effects. This study aims to conduct Preliminary Phytochemical Screening, Phytochemical investigation of some bioactive constituents, and isolation of new compounds from Iraqi Murraya paniculata. It is worth noting that no previous phytochemical survey has been conducted on this plant in Iraq. The entire plant underwent a process of defatting using n-hexane for 48 hours. The materials with reduced fat content were extracted using the hot technique (Soxhlet) in 85% methanol. Subsequently, the extract was fractionated employing solvents with varying polarity, such as petroleum ether, chloroform, and ethyl acetate. A preliminary phytochemical screening was conducted using established procedures. The petroleum ether, chloroform, and ethyl acetate fractions underwent high-performance liquid chromatography (HPLC) analysis using authenticated standards. Preparative layer chromatography was employed to isolate a novel chemical from the chloroform fraction. The isolated compound was identified using FT-IR and 1HNMR. The initial tests suggest the existence of alkaloids, flavonoids, steroids, coumarins, and other secondary metabolites. The chromatographic and spectroscopic analyses reveal the occurrence of various phytochemicals in different fractions of Murraya paniculata as follows: the petroleum ether fraction contains stigmasterol; the chloroform fraction contains aegeline and a newly isolated and identified alkaloid called severifoline; and the ethyl acetate fraction contains apigenin, auraptene, luteolin,5,7,3’,4’-tetramethoxy flavanone and methyl 2,5-dihydroxycinnamate. These findings will be of great value to phytochemists and pharmacologists in their future efforts to develop new active compounds from this plant, considering its notable pharmacological activity.